Mahākavi Sūradāsa : Sūradāsa ke kāvya, jīvana, aura bhakti kā antaraṅga vivecana - Vājapeyī, Nandadulāre, 1906-1967 (SAMP early 20th-century Indian books project ;, 1952)
On the life, works, and philosophy of Sūradāsa, 1483?-1563?, Hindi and Braj saint poet.